Development of chocolate with cacao (Theobroma cacao) nibs. - Quilantang, Reyna Fe Napata
Dark chocolate with cacao nibs was developed. In a survey conducted, 52% out of 130 respondents preferred dark chocolate over milk chocolate. Five (5) formulations of base chocolate which consists of a fixed amount of cocoa liquor and varying amounts of sugar were made. Among the five formulations, F4 with one part cocoa liquor and 2 parts sugar was preferred. Cacao nibs were incorporated in the base chocolate. Chocolate with 10% cacao nibs (CCN) was the most preferred formulation among the three. CCN had 1.41±0.07% moisture content, 6.03±0.14% protein, 19.74±0.85% fat, 2.15±0.37% ash, 8.36±1.35% crude fiber and 62.46±0.99% carbohydrates. CCN had a pH of 6.26±0.001, total soluble solids of 33.67±1.63% TSS, water activity of 0.44±0.001, and tiitrable acidity of 0.045. CCN has moderate bitterness and cocoa aroma, slight nut-like flavor, slightly grainy in texture and dark brown in color. High school and college students (13-23 years old) preferred the product more. Out of 187 respondents, 39% like the product moderately and 32% liked it extremely.